Efeito escala e integridade superficial no microfresamento da liga de níquel inconel 718 - Oliveira, Déborah de (2019)
Micromachining is a process defined by its small dimensions, however it can not be considered a simple reduction of the macro process, since the tool cutting edge radius is even greater than the minimum chip thickness, generating the so-called size effect. This effect causes the process specific energies to be high and therefore there is a great influence of the material microstructure. Regarding the material, Inconel 718 is a refractory superalloy known for its good thermomechanical properties, but low machinability, which is worsened in micromachining, mainly due to the high wear rates of the micromill and the difficulty in generating chips. The objective of this work was to study the machinability of Inconel 718, through micromilling tests varying the cutting speed, the feed per tooth, the depth of cut and the application of cutting fluid. The following outputs were selected for evaluation: surface quality, Ra roughness, burr height, micromill wear, acoustic and vibration signals, cutting forces and chips. In addition, statistical analyzes and computer simulations were performed. The main results include: the 1000% increase in the machined length for tool-life when applying cutting fluid for vc = 25.1 m/min and 75.4 m/min and 500% for vc = 50.3 m/min. It was verified that in the presence of fluid there is no formation of bottom burrs and practically no material adhered in the machined slot. It was concluded that the minimum chip thickness is 5.0 µm, below this value the slot quality deteriorates and forces are generated in the opposite direction of the cut due to the high plowing. For machining with high feeds per tooth values, it was observed that the burr decreases when increasing the feed per tooth, the opposite effect was obtained for roughness Ra. Inconel 718 micromilling generates three main types of chips: helical, formed on the main cutting edge, tape-like, formed on the secondary cutting edge, and dendritic type spheroidal chip which are small, high-energy chips that oxidize to form spheres.